ChemInform Abstract: Nano‐Copper Catalyzed Highly Regioselective Synthesis of 2, 4‐Disubstituted Pyrroles from Terminal Alkynes and Isocyanides. Issue 1 (17th December 2015) - Tiwari, Dipak Kumar; Pogula, Jaya; Sridhar, B.; Tiwari, Dharmendra Kumar; Likhar, Pravin R.
Abstract: The copper‐catalyzed cycloaddition of aromatic alkynes (I) with 2‐isocyanoacetate (II) leads to 4‐aryl‐1H‐pyrrole‐2‐carboxylates (III).